Big government and your Big Mac : Analyzing the impact of corn and soybean subsidies on US meat markets - Chudler, Nadav David (SLU/Dept. of Economics, 2016)
Extensive literature exists regarding the externalities of industrial meat production in the United States. There is also a belief that the growth of these production systems were facilitated by high levels of subsidies for corn and soybean, the primary crops, or byproducts of which are used to feed livestock. This in turn suggests a linkage between feed crop subsidies and the externalities from meat production. Regardless of any impact these subsidies may have had on development of industrial meat production the only subsidies currently of relevance for corn and soybean are for insurance rate premiums. This paper proposes to examine the impact of these subsidies on the US meat markets using a modified stochastic equilibrium displacement model originally developed by Dhoubhadel, Azzam, and Stockton. The results found that these subsidies have a minimal effect on meat production levels. Therefore, if a reduced meat sector is desirable then other avenues, such as improved regulation or taxation, should be pursued.